INTEGRASI MEDIA ICT KE DALAM PENDEKATAN COLLABORATIVE LEARNING UNTUK MENINGKATKAN IKLIM KELAS DAN MOTIVASI BELAJAR BIOLOGI SISWA KELAS X-1 SMA BATIK 1 SURAKARTA - Febriyanti, Shelli; Prayitno, Baskoro Adi; Sugiharto, Bowo (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? The research is classroom action research. The aim is to improve class climate and student?s learning motivation in class X-1 of SMA Batik 1 Surakarta by integrating ICT media into collaborative learning approach that implemented in biology learning process. This act is based on the biology learning process observation in class X-1 where researcher found some learning problems. They are class climate and student?s learning motivation. Based on literatures study, we give solution to improve them by integrating ICT media into collaborative learning approach. Main data is collected from questioner and observation. While additional data is taken from interview, documentation, and test. Validation data uses triangulation and expert team. The act of research consists of two cycles. Research target is 65% for class climate and 60% for student?s learning motivation. The result of cycle 1 describes that generally the research target is accomplished not optimally. Percentage of class climate is 65,54% and student?s learning motivation is 72,58%. The result of cycle 2 describes that generally the research target is accomplished optimally. Percentage of class climate is 73,65% and student?s learning motivation is 77,30%. This cycle stopped here because targets accomplished optimally. Class climate and student?s learning motivation increase well. This learning approach can improve targets because it?s syntax support student?s interaction and interest. The conclusion of this research describes that integration ICT media into collaborative learning approach can improve class climate and student?s learning motivation in class X-1 of SMA Batik 1 Surakarta. Keywords: ICT Media, collaborative learning, class climate, student?s learning motivation